UPAYA PENINGKATAN KUALITAS LAYANAN LAUNDRY MELALUI PENGELOLAAN KELUHAN TAMU OLEH LAUNDRY ATTENDANT DI BEVERLY HOTEL BATAM - Stevani Natalina; Yudha Wardhani (Journal of Innovation Research and Knowledge, 2025)
This study examines efforts to improve hotel laundry service quality through guest complaint handling by laundry attendants at Beverly Hotel Batam. The research problem is the increasing number of laundry complaints such as late returns, inadequate cleaning, damage, missing items that threaten guest satisfaction. Objectives are to identify complaint types, describe complaint-handling processes, and analyze how attendants’ actions contribute to service quality improvement. A descriptive qualitative design was used with in-depth interviews, observation, and document review. Findings show attendants perform rapid responses, empathetic communication, problem verification using log books/photos, re-washing or escalating to supervisors, and participate in monthly training and evaluation. These practices improve recovery and guest satisfaction but are constrained by staffing levels, equipment condition, and limited authority for compensation. Conclusion: effective complaint management by laundry attendants positively impacts laundry service quality. Recommendations include increasing staff, updating equipment and Standard Operational Procedure, and ongoing technical and communication training.